2021
DOI: 10.1111/apa.16094
|View full text |Cite
|
Sign up to set email alerts
|

Birth order and socioeconomic disadvantage predict behavioural and emotional problems at age 3 years

Abstract: Repeated classroom studies have demonstrated increasing rates of psychological and psychosomatic symptoms in school children in Sweden over time since the 1980s, with the most pronounced increase in female adolescent pupils. 1 This trend has been accompanied by a considerable increase in the use of child and adolescent psychiatric care, particularly with diagnoses of anxiety and depression, 2 and a less favourable trend in youth suicides than other countries in northern Europe. 1 These worrying trends have mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Further, a higher proportion of participating parents were seeking parenting support for boys. As studies suggest that boys express more regulation difficulties than girls during preschool-age [ 62 , 94 , 95 ], this uneven gender distribution might also indicate higher behaviour problems among the children in the Triple P groups. The Triple P system is designed as a stepped intervention, providing more intense parenting support at higher levels.…”
Section: Discussionmentioning
confidence: 99%
“…Further, a higher proportion of participating parents were seeking parenting support for boys. As studies suggest that boys express more regulation difficulties than girls during preschool-age [ 62 , 94 , 95 ], this uneven gender distribution might also indicate higher behaviour problems among the children in the Triple P groups. The Triple P system is designed as a stepped intervention, providing more intense parenting support at higher levels.…”
Section: Discussionmentioning
confidence: 99%
“…The varying perceptions of the child's abilities can be explained by the fact that the child is in different contexts, in interaction with people with different demands and expectations. In addition, the parents' mental health, socioeconomic condition, other mother tongue and cultural contexts (57)(58)(59) may affect what the parents tell the CHC psychologist about their child's mental psychosocial health.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, although only a small number of studies which included exclusively young children (0-7 years), all studies except one [64] showed that children in nuclear families and SPC families had equal outcomes [12,50,51,60,63]. In contrast, children in LPC families had the worst outcomes in four of the six (60.0%) studies.…”
Section: Plos Onementioning
confidence: 95%